Effectiveness of the LUCAS device for mechanical chest compression after cardiac arrest: systematic review of experimental, observational and animal studies. Issue 12 (7th March 2012) - Gates, Simon; Smith, Jessica L; Ong, Giok J; Brace, Samantha J; Perkins, Gavin D
Abstract : Context: The LUCAS mechanical chest compression device may be better than manual chest compression during resuscitation attempts after cardiac arrest. Objective: To summarise the evidence about the effectiveness of LUCAS. Data sources: Searches of 4 electronic databases, reference lists of included studies, review articles, clinical guidelines, and the manufacturer's web site. No language restrictions were applied. Date of last search: September 2011. Study selection: All studies, of any design, comparing mechanical chest compression using LUCAS with manual chest compression, with human or animal subjects. Studies published only as abstracts were included. Manikin studies, and case reports or case series, were excluded. Data extraction: Data were extracted on study methodology and outcomes, including return of spontaneous circulation, survival, injuries caused by resuscitation, and physiological parameters. Results: 22 papers reporting 16 separate studies were included. There was one randomised trial, nine cohort studies, 2 before/after studies and 4 animal studies. No meta-analyses were performed because of high risk of bias and heterogeneity in the study designs. Animal studies suggested an advantage to LUCAS in terms of physiological parameters, but human studies did not suggest an advantage in ROSC or survival. Existing evidence is low quality because most studies were small and many were poorly reported. Conclusions: There is insufficient evidence to make any recommendations for clinical practice. Large scale, high quality randomised trials of LUCAS are needed. Studies that have so far been published only as abstracts should be reported fully.